Experimental study of moment sharing in multi-joist timber-concrete composite floors from zero load up to failure. (20th November 2019) - Mudie, J.; Sebastian, W.M.; Norman, J.; Bond, I.P.
Highlights: In multi-joist TCCs, transverse distribution of midspan moments differs strongly from that of support reactions. Novel instrumentation used to back-calculate midspan moment sharing from tests. Expanded steel mesh plate showed good stiffness and ductility as a shear connector. Abstract: The critical T-sections of multi-joist timber-concrete composite (TCC) floors must be designed at ultimate for support shear force and midspan moment, both of which are influenced by transverse sharing, but to different extents. Prior experimental work has investigated only support reaction sharing and only up to serviceability loads. The present experimental study builds on that status quo by quantifying also moment sharing, via strain gauge layouts at quarter-span and midspan, along with reaction sharing via load cells at the supports of a multi-joist TCC specimen, over the entire load range up to failure. Use of steel mesh connectors bonded into hardwood laminated veneer lumber joists, and near geometric resemblance to a real building TCC floor recently built in London, were novel features of the specimen. The results show that midspan moment and reaction sharing both vary nonlinearly with load, but in distinctly different ways from each other (with up to almost 20% difference observed between them), in the progression between the uncracked, cracked and connection ductility regimes. In this approach reliable assessment of moment sharing depends on the quality of the recorded strains. Accordingly, the strain data were shown to be of high quality by converting these data to internal stress resultants that were then found to satisfy longitudinal equilibrium. It is concluded that this strain gauge layout is useful for future work aimed at building a database of transverse sharing of moments in TCCs.